The Indoleamine-2,3-Dioxygenase (IDO) Inhibitor 1-Methyl-D-tryptophan Upregulates IDO1 in Human Cancer Cells - Opitz, Christiane A.; Litzenburger, Ulrike M.; Opitz, Uta; Sahm, Felix; Ochs, Katharina; Lutz, Christian; Wick, Wolfgang; Platten, Michael (PLOS ONE, 2011)
1-methyl-D-tryptophan (1-D-MT) is currently being used in clinical trials in patients with relapsed or refractory solid tumors with the aim of inhibiting indoleamine-2,3-dioxygenase (IDO)-mediated tumor immune escape. IDO is expressed in tumors and tumor-draining lymph nodes and degrades tryptophan (trp) to create an immunsuppressive micromilieu both by depleting trp and by accumulating immunosuppressive metabolites of the kynurenine (kyn) pathway. Here we show that proliferation of alloreactive T-cells cocultured with IDO1-positive human cancer cells paradoxically was inhibited by 1-D-MT. Surprisingly incubation with 1-D-MT increased kyn production of human cancer cells. Cell-free assays revealed that 1-D-MT did not alter IDO1 enzymatic activity. Instead, 1-D-MT induced IDO1 mRNA and protein expression through pathways involving p38 MAPK and JNK signalling. Treatment of cancer patients with 1-D-MT has transcriptional effects that may promote rather than suppress anti-tumor immune escape by increasing IDO1 in the cancer cells. These off-target effects should be carefully analyzed in the ongoing clinical trials with 1-D-MT.